#### Answer

6

#### Work Step by Step

$\lim\limits_{x \to 2}x(x - 1)(x + 1)$ = [$\lim\limits_{x \to 2}x$][$\lim\limits_{x \to 2}(x - 1)$][$\lim\limits_{x \to 2}(x + 1)$ =
= 2 x 1 x 3 = 6

Published by
Wiley

ISBN 10:
0-47064-772-8

ISBN 13:
978-0-47064-772-1

6

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.